Evaluation of the effects of zinc supplementation on the symptoms and duration of the disease in acute viral gastroenteritis - Mehmet Emin Celikkaya; Cigdem El (Family Practice and Palliative Care, 2019)
Introduction: Acute viralgastroenteritis is the second most common cause of high morbidity and mortalityin childhood. Viral gastroenteritis is the most common cause of severe diarrheaand associated hospitalizations especially in toddlers. It has been shown thatthe administration of 20 mg of zinc daily during acute diarrhea reduces theduration of watery diarrhea by 25% and it has been reported to have protectiveand therapeutic effects in the acute period. The aim of this study is toretrospectively determine the beneficial effects of oral zinc supplementationon the severity and duration of complaints of toddlers who were treated in ourclinic with the diagnosis of acute viral gastroenteritis.Methods: Toddlers who were hospitalizedin the Department of Pediatrics for acute viral gastroenteritis between October2016 and March 2018 were included in the study. The study was retrospective andthe data of the patients were obtained from the patient files. The diagnosis ofacute viral gastroenteritis was made by detecting the adenovirus-rotavirusantigen in the fresh stool specimens. The patients were divided into twogroups. Group 1: patients who received zinc supplementation in addition tosupport treatment. Group 2: patients who received only supportive therapy.Results: The mean number of vomiting was3.60 / day and watery diarrhea was 5.20 / day in group-1 while number ofvomiting was 6.1 / day and watery diarrhea was 8.9 / day in group-2 in the 36thhour during treatment. The tolerability of oral feeding at 36 th hour was49.39% ( 41) in group-1 and 45.07% (32) in group-2. The mean number of vomitingand watery diarrhea in group-1 cases at 72th hours was 1.2 / day and 4.30 /day, while in group-2 cases, 3.90 / day and 7.20 / day.Conclusions: Although the physiopathology of the effects of zinc on gastroenteritisis not yet fully understood, diarrhea is seen both as a cause and as a resultof zinc deficiency. The fact thatpatients with gastroenteritis benefit from zinc support suggests that zincenhances this effect by increasing intestinal immunity.